A STUDY ON THE EFFECT OF CONTENT SCHEMATA ON READING COMPREHENSION PERFORMANCE - Fridolin J. P Kukus (KOMPETENSI, 2021)
This study aims at describing the effect of the third semester students' religious knowledge on their literal and inferential comprehension. This study is experimental since it is experimental in nature. The design used is called post-test only controlled group design. The analysis presented statistically. In conducting the analysis the writer applied statistical technique using t-test because the data were in the form of test scores representing the third semester students' literal and inferential reading comprehension performance. The data representing the third semester students' literal and inferential reading comprehension performance were collected using reading test in multiple choice format. Two texts on the basis of which test items were developed dealt with Christmas Eve and Ramadhan Eid. These two texts were selected for the two celebrations are most popular religious events in Christian and Moslem religious group. The sample of this research were taken from the third semester students of English Education Department FBS UNIMA in the academic year of 2014/2015. The total number of students is 30 consist of 15 students of Christian and 15 of Moslem. The analysis shows that the third semester students' content schemata significantly affect their literal and inferential comprehension of religious-related texts. Other researches concerning the effect of content schemata still need to be conducted in order to get more accurate or valid information